Possession - Fremlin, Celia (Victor Gollancz, 1969)
In this mystery novel, Possession, 19-year-old Sarah Erskine has a history of loser boyfriends. Is she one of those forgiving types or does she just have poor judgement? Well the jury is out on that question, but when Sarah announces that she’s marrying her latest, Mervyn, a 31-year-old accountant who lives with his mummy, Sarah’s mother, Clare, the novel’s spiky narrator, has mixed feelings. On one hand, he’s so much older than Sarah. Then there’s that red flag: still living with mummy… but he does have a decent job and seems the reliable type. This is a clever, multi-layered novel which examines parenthood, the difficulties of remaining clear-eyed about one’s children, and the responsibility parents have towards children. At what point should parents ‘let go’ of their children and watch them make their mistakes?